Аутсорсинг управления ресурсами медицинских учреждений - Гайдаенко, О. В.; Кошкин, К. В.; Удовиченко, П. Н. (НТУ "ХПИ", 2015)
Проведен анализ предметной области, выявлены проблемы существующей структуры здравоохранения эффективного использования медицинского оборудования. Предложена новая модель эффективного использования медицинского оборудования.

The analysis of the subject area is conducted, problems in the existing health structures effective use of medical equipment are identified. A new model for the effective use of medical equipment is proposed.
The Outsourcing as a model for the effective use of medical equipment
Keywords: система здравоохранения; медицинские услуги; управление медицинским учреждением; медицинское оборудование; морфологические исследования; medical services; health management organizations; equipment; outsourcing; morphological studies